An Observational Study on Early Empiric versus Culture-Directed Antifungal Therapy in Critically Ill with Intra-Abdominal Sepsis - Winnie Lee; Yixin Liew; Maciej Piotr Chlebicki; Sharon Ong; Pang Lee; Andrea Kwa (Critical Care Research and Practice)
Objective. To compare early empiric antifungal treatment with culture-directed treatment in critically ill patients with intra-abdominal sepsis. Methods. A prospective observational cohort study was conducted between August 2010 and July 2011, on SICU patients admitted after surgery for gastrointestinal perforation, bowel obstruction or ischemia, malignancy and anastomotic leakages. Patients who received antifungal treatment within two days of sepsis onset were compared to patients who received culture-directed antifungal treatment in terms of mortality rate and clinical improvement. Patients’ demographics, comorbidities, severity-of-illness scores, and laboratory results were systematically collected and analysed. Results. Thirty-three patients received early empiric and 19 received culture-directed therapy. Of these, 30 from the early empiric group and 18 from culture-directed group were evaluable and analysed. Both groups had similar baseline characteristics and illness severity. Patients on empiric antifungal use had significantly lower 30-day mortality (P=0.03) as well as shorter median time to clinical improvement (P=0.025). Early empiric antifungal therapy was independently associated with survival beyond 30 days (OR 0.131, 95% CI: 0.018 to 0.966; P=0.046). Conclusion. Early empiric antifungal therapy in surgical patients with intra-abdominal sepsis was associated with reduced mortality and warrants further evaluation in randomised controlled trials.